Phacomatosis cesioflammea in a 5-week-old infant - Khushboo Gupta; Lalit Kumar Gupta; Asit Mittal; A K Khare; Sharad Mehta; Manisha Balai (Wolters Kluwer Medknow Publications, 2016)
A 5-week-old male infant presented with extensive lesions of nevus flammeus and Mongolian spots affecting the face, trunk, buttocks and extremities. In addition, the child had ocular melanosis and a café-au-lait spot on the trunk. The case is being reported on account of its rarity.